Impact of varying Li+ concentration on the upconversion emission and temperature sensing characteristics of YVO4: Tm3+/Yb3+ phosphor - Thakur H.; Singh S.; Gathania A.K.; Kumar Singh S.; Kumar I.; Kumar Singh R. (My University, 2025)
A series of Li+ codoped YVO4: Tm3+/Yb3+ phosphors were prepared by Pechini sol–gel reaction technique. Structural study of the material confirms the crystal structure of the prepared samples and also gives information about the crystallite size and phase purity with the variation of Li+ ion concentrations. Emission peaks around ∼ 476, and ∼ 799 nm corresponds to the 1G4→3H6, and 3H4→3H6 transitions, which could be seen under irradiation of NIR (980 nm) laser light. Li+ (10 mol%) codoped sample shows maximum upconversion. Li+ doping significantly increases the up-conversion emission intensities by more than 5 times for emission peaks around 476 nm and 799 nm.The possible explanation for the increase in UC (Upconversion) emission intensity is attributed to both improved crystallinity and crystal field modification around Tm3+ ions. The variation of UC emission spectra with respect to pump power was observed to investigate the underlying UC luminescent mechanism in YVO4: Tm3+/Yb3+ codoped with Li+ (10 mol%). The multiphoton involvement is observed in the power-dependent study of upconverted blue and NIR emission bands. Widely used fluorescence intensity ratio (FIR) technique was used to evaluate the temperature sensing capability of the optimized Li+ codoped phosphor. The FIR study of Stark components 3F2, and 3H4 levels indicates that this material is an efficient material for temperature sensing. The optimized sample, doped with Li+, exhibits relative sensitivity of 0.78% K−1 at a temperature of 548 K. This material have utility in both light-emitting diodes and as a temperature-sensing probe. © 2023 Elsevier B.V.